O18-3 A cross-sectional study of changes in markers of immunological effects and lung health due to exposure to multi-walled carbon nanotubes. (1st September 2016) - Vlaanderen, Jelle; Pronk, Anjoeka; Hosgood, Dean; Rothman, Nathaniel; Hildesheim, Allan; Silverman, Debra T; Spaan, Suzanne; Kuijpers, Eelco; Godderis, Lode; Hoet, Peter; Lan, Qing; Vermeulen, Roel
Abstract : Background: Multi-Wall Carbon nanotubes (MWCNTs) are increasingly used in a multitude of applications, resulting in occupational exposure. Evidence from animal and mechanistic studies indicates that the lung and immune system are potential targets for MWCNT-related health effects. Methods: In phase 1 of the study, we assessed lung function and exhaled nitrogen oxide (FENO), and collected peripheral blood among 22 workers at a MWCNT producing facility and 39 age- and gender-matched, unexposed controls. Blood samples were assayed for complete blood cell counts, 51 immune markers and three pneumoproteins: CC-16, SP-A, and SP-D. Based on quantitative personal exposure assessment, MWCNT production workers were categorised into operators (higher exposure) and lab workers (lower exposure). Six months later (phase 2) the study was repeated among a subset of workers. Results: We observed significant depression in FENO among operators compared to controls during phase 1 (p = 0.01; not assessed in phase 2). We observed significant depression in neutrophils (p = 0.01) and significant elevation in monocytes (p = 0.01), mean platelet volume (p = 0.004), and immature platelet fraction (p = 0.05) among operators compared to controls in phases 1 and 2. We observed significant upward trends with exposure for CXCL11 (p = 0.02), CCL20 (p = 0.005), FGF-2 (p = 0.05), and sIL-1RII (p = 0.0004), and significant downward trends for IL-16 (p = 0.03), CCL27 (p = 0.02) and CTACK (p = 0.02). The associations with CCL20, FGF-2, and sIL-1RII were replicated in phase 2. Several associations remained significant after multiple testing correction (q < 0.2). We observed no effect of exposure to MWCNT on FEV1, FVC, and FEV1/FVC or pneumoproteins. Conclusion: We report some indications of early effects of occupational exposure to MWCNTs on lung health and the immune system, but observed no effect on clinically relevant outcome lung function. Our findings need to be verified in large studies that apply high quality personal exposure assessment methods. Such studies will require collaboration between researchers and MWCNT producers.